Profil model mental siswa sekolah menengah atas tentang konsep sel - Agustina, Siti Komariah; Rahman, Taufik; Hamdiyati, Yanti (Department of Biology Education, Universitas Pendidikan Indonesia, 2020)
The concept of cell is one of material that is quite complicated because it contains abstract concepts such as cell organelles and the mechanism of transport of substances. This study aims to identify the mental models of high school students about the concept of cells represented in written, oral, and picture forms. The method used is descriptive method. In this research, the method use to find mental model of senior high school studets in cells subject. The students are given diagnostic test, as multiple choice, visual test, and oral test which used as students’ mental model parameter. Majority grade XI students of science in senior high school have scientific model, in other words written ideas which refer to the concept with scientific understanding or have basic theory. It can be find in the result: 40% scentific for writing test, 53% scientific for oral test, and 40% scientific for drawing test. Whereas, grade XI students of science in private high school, the students have experience model which shows from their reprecentation which based on analogy. It can be find in the result: 42% experience for writing test, 57% experience for oral test, and 42% experience for drawing test.